Pelanggaran Harga Dasar Gabah: Studi Empiris di Kabupaten Pinrang (LEGAL DIALOGICA, 2025)
This study aims to determine the form of alleged violations of criminal law that occur in the system of buying and selling grain that is not in accordance with the basic price set by the government and to find out what factors hinder the government in supervising and enforcing the basic price of grain so that there are alleged violations of criminal law in buying and selling grain. This research uses empirical legal research methods, with research locations in Pinrang Regency. Data collected through interview techniques and literature studies which were then analyzed. The results showed that the alleged violation of criminal law that occurred in the grain buying and selling system that was not in accordance with the basic price set by the Pinrang Regency government reflected the discrepancy between the expected basic price policy and the reality in the field. This includes the purchase of grain below the basic price, neglect of protection for farmers, and the government's inability to provide effective supervision.  As a recommendation, the Pinrang district government needs to improve its supervision of grain buying and selling practices to ensure that the price floor is consistently applied and to reduce farmers' dependence on middlemen who take advantage of their position, the government should implement intensive education and socialization programs on the importance of the price floor and farmers' rights.Abstrak:Penelitian ini bertujuan untuk Untuk mengetahui bentuk dugaan pelanggaran hukum pidana yang terjadi dalam sistem jual beli gabah yang tidak sesuai dengan harga dasar yang ditetapkan pemerintah Serta untuk mengetahui faktor apa saja yang menghambat pemerintah dalam mengawasi dan menegakkan harga dasar gabah sehingga terjadi dugaan pelanggaran hukum pidana dalam jual beli gabah. Penelitian ini menggunakan metode penelitian hukum empiris, dengan lokasi penelitian di Kabupaten Pinrang. Data yang dikumpulkan melalui teknik wawancara dan Studi Pustaka yang kemudian dianalisis. Hasil Penelitian Menunjukkan bahwa dugaan pelanggaran hukum pidana yang terjadi dalam sistem jual beli gabah yang tidak sesuai dengan harga dasar yang ditetapkan oleh pemerintah Kabupaten Pinrang mencerminkan ketidaksesuaian antara kebijakan harga dasar yang diharapkan dengan kenyataan di lapangan. Hal ini mencakup pembelian gabah di bawah harga dasar, pengabaian perlindungan terhadap petani, serta ketidakmampuan pemerintah dalam pengawasan yang efektif.  Sebagai rekomendasi pemerintah Kabupaten Pinrang perlu meningkatkan pengawasan terhadap praktik jual beli gabah untuk memastikan bahwa harga dasar yang ditetapkan dapat diterapkan secara konsisten serta untuk mengurangi ketergantungan petani terhadap tengkulak yang memanfaatkan posisi mereka, pemerintah harus melaksanakan program pendidikan dan sosialisasi yang intensif mengenai pentingnya harga dasar gabah serta hak-hak petani.